Relationship Between Glass Ceiling Syndrome and Self-Efficacy; in Health Sector - Kılıç, Taşkın (European Journal of Multidisciplinary Studies, 2017)
Objective of the study: In the line management of the busines life, women’s taking a back seat more than men, in related literature, is entitled to “Glass Ceiling” term. Objective of this study is to specify the perception of Glass Ceiling of women work in health sector in proportion to men work in same sector, also, to identify relation between self-efficacy term which has important effects on career success and Glass Ceiling syndrome. Methodology of the study: 100 managers, 100 employee work in the institutions of the ministry of health and 100 new graduate (not assigned yet management trainee), in total, 300 people form the research sample. The research was conducted by face-to-face survey. The obtained data were subjected to analysis in SPSS software. Result of the study: as a result of the research, it has been found that women have more Glass Ceiling syndrome according to men. Between self-efficacy and glass ceiling syndrome, scientifically no meaningful results have been obtained on age and title.